(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The current study was carried out to identify the bacterial species in the faecal samples of 20 diarrhoeic sheep and to observe their sensitivity to different antibiotics. This investigation was performed by collecting diarrhoeal samples from the sheep (n=20) under goat and sheep research farm of Bangladesh Livestock Research Institute (BLRI), Savar, Dhaka, Bangladesh. The average age and body weight of the animals were 25 days and 2.5 kg respectively. Of the bacteria responsible for diarrhoea in case of sheep, Escherichia coli alone was found in 6 samples (30%), Escherichia coli combined with Proteus mirabilis was found in 12 samples (60%), and no bacteria could be detected in 2 of the 20 samples tested. Both the bacteria were highly sensitive to ceftriaxone, and moderately sensitive to ciprofloxacin and gentamicin. It could be stated that ceftriaxone is the antibiotic of first choice for the treatment of diarrhoea in sheep, where Escherichia coli is suspected to be the principal causal agent of diarrhoea. Res. Agric., Livest. Fish.2(3): 453-457, December 2015